The MOOCs: origin, characterization, principal problems and challenges in Higher Education - Lourdes Normandi Atiaja Atiaja; Rey Segundo Guerrero Proenza (Je-LKS: Journal of E-Learning and Knowledge Society, 2016)
MOOCs (Massive Open Online Courses) are an innovation that have attracted public academic attention in recent times, and which have resulted in the evolution of e-learning (electronic learning) and so far have not achieved their expectations in Higher Education. This is due to the fact that from the outset these courses have faced a number of problems and questions regarding their acceptance, credibility, quality, methods of assessment, learning outcomes and more; which has generated controversy among their opponents, fans and even the creators of MOOCs. This work forms part of a doctoral investigation; in essence these are the results of the preliminary and exploratory stages in the research process, in which projections on the solution of some problems will be included. MOOCs: Their evolution, problems and challenges up to 2015, will surely help to minimize the high dropout rates of students in MOOCs, supported by mobile technology.